Participatory Training and Battery-Powered Milking - Nurhadi, Slamet; Ridzki, Imron; Wiwaha, Sigit Setya; Duanaputri, Rohmanita; Effendrik, Popong; Gumilang, Binar Surya (Research Horizon, 2025)
Smallholder goat farmers in Jabung Village, Malang Regency, face significant challenges related to manual milking, including prolonged labor time and limited access to appropriate technologies. This study aimed to evaluate the effectiveness of a portable, battery-powered milking device in enhancing labor efficiency, technical knowledge, and economic outcomes for these farmers. Using a Participatory Action Research (PAR) approach, the research involved 50 farmers through a baseline survey, co-design process, a six-hour training session, and follow-up evaluation. The results showed that the device reduced the average milking time for five goats from 64 ± 4 minutes to 55 ± 3 minutes, indicating a 14% improvement. Farmers’ technical knowledge also increased significantly, from 42% to 85% after training. User satisfaction was high, averaging 4.2 out of 5, with women reporting greater ergonomic benefits. Economically, the device demonstrated an eight-month payback period based on a milk price of 12,000 Indonesian Rupiah per liter. Furthermore, 80% of farmers were able to operate the device independently after training. These findings suggest that the device holds strong potential to improve smallholder productivity and resilience, contributing to Sustainable Development Goals (SDGs) 2 and 7. However, limitations include the small sample size and the absence of data on milk quality, indicating the need for broader, long-term research.